PENINGKATAN HASIL BELAJAR IPAS DENGAN PENERAPAN MODEL TGT BERBANTUAN MEDIA ROKA KELAS IV SD - Mukti, Lola Indra; Ardianti, Sekar Dwi; Ratnasari, Yuni (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
One of the learning models that can be used to improve science learning outcomes is Team Games Tournament. The Team Games Tournament model is one of the cooperative learning methods designed to improve student learning outcomes through group collaboration. Supported by ROKA media as a concrete (real) aid to make it easier for students to understand the material on cultural diversity and local wisdom. The purpose of this study is to determine the improvement in science learning outcomes with the application of the Team Games Tournament model assisted by ROKA media. This study was conducted in class IV SDN Karangrejo 01 with a sample size of 23 students. This study uses quantitative research with the type of Pre-Experimental Design research with the research design of One Group Pretest-posttest Design. Data collection techniques include observation techniques, interviews, documentation. Data analysis used is Hypothesis Testing (N-Gain Test). The calculation of the N-Gain test results shows an increase of 0.58 with a moderate increase category. This finding shows that there is an increase in the results of learning science through the implementation of the Team Games Tournament model assisted by ROKA media for fourth grade students of SDN Karangrejo 01. ABSTRAKSalah satu model pembelajaran yang dapat digunakan untuk meningkatkan hasil belajar IPAS adalah Team Games Tournament. Model Team Games Tournament merupakan salah satu metode pembelajaran kooperatif yang dirancang untuk meningkatkan hasil belajar siswa melalui kerja sama kelompok. Di dukung dengan media ROKA sebagai alat bantu berbentuk konkret (Nyata) untuk mempermudah siswa memahami materi keberagaman budaya dan kearifan lokal. Tujuan penelitan ini mengetahui peningkatan hasil belajar IPAS dengan penerapan model Team Games Tournament berbeantuan media ROKA. Penelitian ini dilakukan di kelas IV SDN Karangrejo 01 dengan jumlah sampel penelitian 23 siswa.penelitian ini menggunakan penelitian kuantitatif dengan jenis penelitian Pre-Eksperimental Design dengan desai penelitian One Group Pretest-posttest Design. Teknik pengumpula data meliputi teknik observasi, wawancara, dokumentasi. Analisis data yang dipakai yaitu Uji Hipotesis (Uji N-Gain). Perhitungan dari hasil uji N-Gain menunjukkan adanya peningkatan sebesar 0,58 dengan kategori peningkatan sedang. Temuan ini menunjukkan bahwa terdapat peningkatan hasil belajar IPAS melalui penerapan model Team Games Tournament berbantuan media ROKA siswa kelas IV SDN Karangrejo 01.